2020
DOI: 10.21203/rs.3.rs-27756/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic interventions in Australian primary care, youth mental health settings for young people with Borderline Personality Disorder or borderline traits

Abstract: Background This study aimed to investigate what therapeutic interventions were being applied by clinicians working with young people with a diagnosis of Borderline Personality Disorder or borderline traits in Australian primary mental health care settings. Given the current lack of evidence-based guidelines for treatment with this client population, investigating what is being implemented is needed. The study also aimed to determine whether the interventions clinicians are using are effective in reducing dist… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…A recent study of 76 Australian Headspace youth mental health centres found clinicians recorded ‘borderline personality traits’ as the presentation in less than 1% of referrals. 6…”
Section: Alliance Proposal For Early Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of 76 Australian Headspace youth mental health centres found clinicians recorded ‘borderline personality traits’ as the presentation in less than 1% of referrals. 6…”
Section: Alliance Proposal For Early Interventionmentioning
confidence: 99%
“…A recent study of 76 Australian Headspace youth mental health centres found clinicians recorded 'borderline personality traits' as the presentation in less than 1% of referrals. 6 Previously, a Global Alliance for Prevention and Early Intervention for Borderline Personality Disorder (hereafter the Alliance) set aspirational goals for the field of youth mental health. 5 It was asserted that early BPD should be detected and treated early in youth (ages from 12 to 25 years).…”
mentioning
confidence: 99%
“…Despite this need for appropriate strategies for early intervention to reduce the short-term burden and prevent long-term disabilities, several studies suggest that current mental health services often do not provide an appropriate response to the health needs of these young persons. Data from the Netherlands (14) as well as Australia (15), show that young persons with BPD remain largely undetected in primary services, are not referred to appropriate treatment and are rarely provided appropriate, evidence-based treatments. Brief psychosocial treatments that are common in primary care seem to be less effective for young people with BPD.…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%
“…Yet, poor or non-response in these young people is the rule rather than the exception. In a study on primary care in Australia for 12-to 25year-olds, for instance, patients with BPD symptoms showed no progress or deteriorated in terms of social and occupational functioning (45%), psychological stress (60%) and quality of life (69%) (15). Importantly, aside from the lack of efficiency in attaining, this approach generated iatrogenic damage in these youngsters as failed treatment attempts lead to disappointment in and distrust of mental health services (18), which may undermine future care seeking or treatment success.…”
Section: Introduction Background and Rationale {6a}mentioning
confidence: 99%